Health education in action against the impacts of Chagas disease (Research, Society and Development, 2020)
Objective: to evaluate the effectiveness of health education by health professionals about Chagas disease. Method: the article was produced through an integrative bibliographic review with a qualitative approach, using the following databases: SCIELO, LILACS, PUBMED, BVS BRASIL and information contained on the Pan American Health Organization (PAHO) website, scientific journals, books made available by the internal library of Faculdade Irecê - FAI and guidelines from the Ministry of Health. 11 years was cut, 2009 to 2020, with inclusion criteria for articles in English, Portuguese and Spanish. Thus, based on content analysis, preceded by thorough reading, approaches related to health education were selected. Results: From the approach of health education in the context of Chagas disease, among the 15 articles it is noticeable that even though it is only cited, superficially cited and not cited, the size of the impact that its theme brings to public health is perceived because it is notorious that it is still necessary to emphasize the relevance of it related to how health professionals conduct it, which is unfortunately seen negatively. Final Considerations: The results obtained in this study identified the need for new scientific research regarding health education on Chagas disease in an academic and / or community environment, considering that the number of researches on this subject is reduced.